Síntese e caracterização das propriedades térmicas e óticas de materiais moleculares conjugados derivados de benzilidenocetonas - Araújo, Alan Ferreira de (2016)
The low molecular weight materials with -conjugated system are widely studied by the academic community and the industry. The properties shown by such systems collaborate are the basis for electro-optical devices such as OLEDs, OFETs and solar cells (organic semiconductors). Liquid crystals compose an important group of low molecular weight materials due to their properties: the order of solid and flow of liquid. In this context, this work presents the synthesis and characterization of the thermal and optical properties of three groups of conjugated compounds derived from benzylidene ketones. The structures of these compound were designed in order to get rod-like structures to form calamitic liquid crystals. The molecules of this work are based on the structure of benzylideneketone 3-methoxy-4-substituted with alkoxyl chains of 4, 10 and 12 carbons. Cyclic and acyclic ketones separate the aromatic rings. The target molecules were characterized by spectrometric methods (IR, 1H and 13C NMR). The thermal properties were investigated by POM, DSC and TGA. One of nine molecules showed mesomorfic phase, three of them did not crystalize on cooling to the room temperature, and the other ones did not show any type of liquid crystalline phase. The thermal decomposition varied from 215 °C to 345 °C. The optical studies were performed in solution by UV spectroscopy. The target compounds exhibited a strong absorption band varying from 330 nm to 370 nm ( = 104 L.mol-1.cm-1) attributed to the -* electronic transitions.